No evidence of structural abnormality of the substantia nigra in adult attention-deficit/hyperactivity disorder: a pilot cross-sectional cohort study - Friedrich, Isabel; von Kuenheim, Daniela; Wozniak, David; Meyer, Patrick; Mauche, Nicole; Huang, Jue; Classen, Joseph; Strauss, Maria; Rumpf, Jost-Julian (Frontiers in Psychiatry, 2024)
Background Abnormal expansion of the echogenic substantia nigra (SN+) is a common observation in Parkinson’s disease (PD) and considered a potential trait marker within this context. However, SN+ was also frequently detected in children diagnosed with attention-deficit/hyperactivity disorder (ADHD), where it has been discussed as a biomarker of maturational dopaminergic dysfunction. Interestingly, ADHD was recently linked to an elevated risk of PD in epidemiological studies, particularly among individuals treated with psychostimulants. Here, we investigated the potential of SN echogenicity as a disease biomarker in adults with ADHD and its relation to psychostimulant treatment. Methods In an exploratory cross-sectional cohort study, we performed transcranial sonography of the SN in 30 adults (mean age 33.3 ± 7.6 years, 19 males/11 females) diagnosed with ADHD according to DSM-V criteria. Results and conclusions In this pilot study, we observed no evidence of structural abnormalities of the SN among adults diagnosed with ADHD, thus questioning the potential of SN+ as a biomarker for ADHD in this population. Moreover, we found no evidence of treatment-related SN echogenicity changes that would link therapeutic psychostimulant use to alterations in the structural integrity of the SN.